Narrating the Intersectionalities of Gender Violence: Editorial - Boonzaier, Floretta (Oñati Socio-Legal Series, 2015)
The telling, sharing and, most critically, the hearing of stories related to gender violence has been a critical part of the project of feminism as well as the refuge movement (Dobash and Dobash 1979, Kelly 1988). This an introduction to a set of papers that represent highlights from the conference entitled "International Congress on Gender Violence: Intersectionalities" in terms of how the intersections of gender violence have been narrated.